2001
DOI: 10.1210/jcem.86.11.8018
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamo-Pituitary Surveillance Imaging in Hypopituitary Patients Receiving Long-Term GH Replacement Therapy

Abstract: Most cases of adult-onset (AO) GH deficiency (GHD) result from the presence of hypothalamo-pituitary tumors or their treatment. GH replacement is now widely used in adults with hypopituitarism, but its effect on hypothalamo-pituitary tumor growth or recurrence is unknown. Anecdotal evidence from early experience of GH replacement in adults documented occasional tumor recurrence, but any relationship of this to the use of GH was unclear. We have now prospectively imaged the pituitary glands of 100 consecutive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Instead, in 100 patients on GH treatment followed prospectively because of sellar tumors, initial tumor growth was found only in one. In this patient, GH replacement was continued, and there was no further enlargement (13).…”
Section: Discussionmentioning
confidence: 78%
“…Instead, in 100 patients on GH treatment followed prospectively because of sellar tumors, initial tumor growth was found only in one. In this patient, GH replacement was continued, and there was no further enlargement (13).…”
Section: Discussionmentioning
confidence: 78%
“…A much larger patient population was studied by Frajese et al (16). They followed a total of 100 patients and 91 of them after irradiation for at least 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Abs et al reported no recurrence in 127 GH-treated adult patients with craniopharyngioma enrolled in KIMS 1994-1996 (3). In the study by Frajese et al, no recurrence was detected in a series of 13 adults with craniopharyngioma treated with GH (66). In a study reporting the results of prospective imaging in 28 consecutive patients with craniopharyngioma and adult-onset GHD, an apparent increase in tumour volume was found in one subject 6 years after the commencement of GH (76).…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 92%
“…In a study of GHD adults, no increase in pituitary tumour recurrence rate was found during an average of 3.6 years of GH replacement as compared with controls not receiving GH treatment (65). In a prospective study of 100 adult-onset GHD patients with pituitary and peripituitary tumours receiving GH replacement therapy, only one case of slight intrasellar tissue enlargement was noted after 1-4 years of follow-up (66). The majority of these patients had received external radiotherapy (66).…”
Section: Hypothalamic-pituitary Tumoursmentioning
confidence: 93%
See 1 more Smart Citation